What is the role of the father in the life and education of a child? (Journal of Parents and Teachers, 2026)
In this article, María Menéndez Ponte analyses the father figure and its evolution within the family. She criticises the traditional father who delegates parenting to the mother and limits himself to contributing financially. She promotes the need for active fatherhood based on equality and collaboration. She highlights that social changes are helping to create new models of fathers who are more involved in raising their children, and argues that both education and domestic tasks should be shared.
Keywords: Fatherhood, Equality, Collaboration, Family and Women.